Analysis of SMA Pembangunan Laboratorium UNP Students’ Chemical Literacy Ability on Reaction Rate Topic by Using Rasch Model - Daffa Diyanah; Eka Yusmaita (Universitas Negeri Padang, 2022)
This study aims to analyze the SMA Pembangunan Laboratorium UNP students’ chemical literacy ability on reaction rate topic according to two theoretical frameworks, that is definition of chemical literacy adapted by Shwartz and levels of scientific literacy developed by Bybee and BSCS. This descriptive research is a quantitative study involving samples of 48 XI grade science students. Data is obtained from a chemical literacy test, then analyzed with the Rasch model. The results showed that students dominated three lowest literacy levels, that is functional scientific literacy (36%), scientific illiteracy (28%), and nominal scientific literacy (22%). Rasch analysis showed that 91.7% of students have negative measure scores with mean of students’ measure scores 1.07 logit. This indicates that students' chemical literacy ability on reaction rate topic are low.